Technological advancement in the era of COVID-19 - Renu, Nishant (SAGE Open Med, 2021)
Regional and local governments worldwide are working tirelessly toward effective ways of addressing the COVID-19 crisis. During this time, the government has had to ensure that they provide full usage of technological means to confront the pandemic and discourse a wide range of COVID-19 related problems. Herein, this article will discuss the application of technical means and the advancement of technology in different sectors as a consequence of the COVID-19 crisis. Further, it highlights how government and health organizations have introduced new policies intending to try to curb the spread of the coronavirus. These new policies, such as lockdowns and social distancing measures, have resulted in technological advancement and new means of interaction with government, businesses, and citizens. Such changes include increased online shopping, as well as robotic delivery systems, the introduction of digital as well as contactless payment systems, remote working, the role of technology in distance learning, Telehealth, 3D Printing, and online entertainment. These technological advancements have been embraced all the way during this pandemic by a few countries around the world, with its limitation in some underdeveloped and developing countries.